The Influence of Work Engagement and Perceived Organizational Support on Organizational Commitment with Job Burnout as a Moderating Variable among Teachers and Education Staff at Binekas Elementary School, Bandung - Rachmi Silviana; Neuneung Ratna Hayati (Dinasti International Journal of Education Management And Social Science, 2025)
This study investigates the influence of work engagement (WE) and perceived organizational support (POS) on organizational commitment (OC), with job burnout (JB) as a moderating variable, among teachers and educational staff at Binekas Elementary School, Bandung. Employing a quantitative-verificative approach with a survey method, data from 60 respondents were analyzed using Moderated Multiple Regression (MMR). The first model demonstrated that WE significantly predicts OC (? = 0.602, p = 0.012), whereas POS was not statistically significant (? = 0.368, p = 0.063). JB did not have a significant direct effect on OC (? = –0.175, p = 0.404). In the second model, the interaction effects between WE and JB (? = 0.015, p = 0.671), as well as between POS and JB (? = 0.016, p = 0.705), were found to be insignificant, indicating that job burnout does not moderate the relationship between WE or POS and OC. The R² change between models was minimal (?R² = 0.008; p = 0.732), further confirming the non-significant moderating effect. These findings highlight the robust role of work engagement in enhancing organizational commitment, while the influence of POS and job burnout remains statistically unsupported within this context.